Genetic accommodation via modified endocrine signalling explains phenotypic divergence among spadefoot toad species - Saurabh S. Kulkarni (Nature Portfolio, 2017)
Genetic accommodation is a potential mechanism for the phenotypic divergence of species. Here, Kulkarni et al. compare endocrine responses of three spadefoot toad species to pond drying and suggest how evolution of mechanisms of developmental plasticity may account for trait variation among species.